Evaluating the Location of Tsunami Sensors: Methodology and Application to the Northeast Coast of Taiwan - Guan-Yu Chen Chin-Chu Liu (Terrestrial, Atmospheric and Oceanic Sciences, 2009)

(untitled)
The "max gain" which is the maximum absolute value of the reciprocal Green's Function of a city vulnerable to tsunami damage is used to evaluate the efficiency of the location for tsunami detecting instruments. The max gain is the correlation between the water elevation variations at the observatory and the vulnerable coastal city. After vulnerable cities are determined, the max gain diagram can be used to determine the most favorable location for observation.